Video capsule enteroscopy in the diagnosis of GIST of the ileum - A. T. Kortieva; V. S. Krushelnitskiy; A. S. Gabriel; V. Yu. Dynko; A. Ya. Guchetl; R. M. Tlekhurai (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to show the effectiveness of video capsule and balloon-assisted enteroscopy in the diagnosis of gastrointestinal stromal tumor of the ileum.METHODS AND MATERIALS. A clinical observation of a patient with a suspected tumor of the small intestine is presented. During the examination, video capsule endoscopy of the small intestine was performed using the Given Imaging capsule. In the ileum, mucosal infiltration and fresh blood were found. Conclusion: tumor of the small intestine. The patient underwent resection of the ileum with a tumor. Histological conclusion: malignant gastrointestinal stromal tumor with moderate mitotic activity and single metastasis to the mesenteric lymph node.CONCLUSION. The difficulty in diagnosing tumors of the small intestine is due to the lack of specific clinical symptoms and the complexity of visualizing the neoplasm. In such cases, it is advisable to include video capsule enteroscopy in the diagnostic algorithm, which according to indications can be supplemented with balloon-assisted enteroscopy by oral or transanal access.